Bone Environment Influences Irreversible Adhesion of a Methicillin-Susceptible Staphylococcus aureus Strain - Reffuveille, Fany; Josse, Jérôme; Velard, Frédéric; Lamret, Fabien; Varin-Simon, Jennifer; Dubus, Marie; Haney, Evan F.; Hancock, Robert E. W.; Mongaret, Céline; Gangloff, Sophie C. (Frontiers in Microbiology, 2018)
Prosthesis and joint infections are an important threat in public health, especially due to the development of bacterial biofilms and their high resistance to antimicrobials. Biofilm-associated infections increase mortality and morbidity rates as well as hospitalization costs. Prevention is the best strategy for this serious issue, so there is an urgent need to understand the signals that could induce irreversible bacterial adhesion on a prosthesis. In this context, we investigated the bone environment and its consequence on a methicillin-susceptible Staphylococcus aureus strain adhesion. Using static and dynamic biofilm models, we tested various bone environment factors and showed that the presence of Mg2+, lack of oxygen and starvation each increased bacterial adhesion. It was observed that human osteoblast-like cell culture supernatants increased bacterial adhesion capacity by 2-fold (p=0.015) compared to the medium control. Moreover, the stimulation of osteoblast-like cells with TNF-α to mimic inflammatory conditions increased bacterial adhesion by almost 5-fold (p=0.003). Interestingly, the effect of osteoblast-like cell supernatants on bacterial adhesion could be counteracted by the activity of synthetic antibiofilm peptides. In conclusion, the bone environment and products of osteoblast-like cells directly influenced S. aureus biofilm formation, which demonstrates an interkingdom communication between host bone cells and bacteria.